Novel Three-Dimensional Interphase Characterisation of Polymer Nanocomposites Using Nanoscaled Topography - Mousa, M.; Dong, Yu (Institute of Physics Publishing Ltd., 2018)
Mechanical properties of polymer nanocomposites depend primarily on nanointerphases as transitional zones between nanoparticles and surrounding matrices. Due to the difficulty in the quantitative characterisation of nanointerphases, previous literatures generally deemed such interphases as one-dimensional uniform zones around nanoparticles by assumption for analytical or theoretical modelling. We hereby have demonstrated for the first time direct three-dimensional topography and physical measurement of nanophase mechanical properties between nanodimeter bamboo charcoals (NBCs) and poly (vinyl alcohol) (PVA) in polymer nanocomposites. Topographical features, nanomechanical properties and dimensions of nanointerphases were systematically determined via peak force quantitative nanomechanical tapping mode (PFQNM). Significantly different mechanical properties of nanointerphases were revealed as opposed to those of individual NBCs and PVA matrices. Non-uniform irregular three-dimensional structures and shapes of nanointerphases are manifested around individual NBCs, which can be greatly influenced by nanoparticle size and roughness, and nanoparticle dispersion and distribution. Elastic moduli of nanointerphases were experimentally determined in range from 25.32 ±3.4 to 66.3±3.2 GPa. Additionally, it is clearly shown that the interphase modulus strongly depends on interphase surface area SAInterphase and interphase volume VInterphase. Different NBC distribution patterns from fully to partially embedded nanoparticles are proven to yield a remarkable reduction in elastic moduli of nanointerphases.